Successful Educational Actions for Inclusion and Social Cohesion in Europe - Flecha, Ramon (Springer, 2016)
This monograph analyses and describes successful educational actions with a specific focus on vulnerable groups (i.e. youth, migrants, cultural groups e.g. Roma, women, and people with disabilities). Concrete data that shows success in school performance in subject matters such as math or language will be provided, as well as children, teachers and families accounts of the impact of this success. Alongside, there is an analysis of the relationship between these children’s educational performance with their inclusion or exclusion from different areas of society (i.e. housing, health, employment, and social and political participation). Many studies have already diagnosed and described the causes of educational and social exclusion of these vulnerable groups. This monograph, however, provides solutions, that is, actions for success identified through the INCLUD-ED project, thus providing both, contrasted data and solid theoretical background and development. Some examples of these actions are interactive groups (or heterogeneous grouping in the classroom with reorganisation of human resources), extension of the learning time, homework clubs, tutored libraries, family and community educative participation, family education, or dialogic literary gatherings. All these actions have been defined as successful educational actions, which mean that they lead to both efficiency and equity. Finally, recommendations for policy and practice are included and discussed.